TAHLIL AL-BUN YAWIYAH FI AL-SYI’RI “SALAMU ‘ALAIKUM” LI ANIES SUSAN (DIRASAH TAHLILIYAH NAQDIYAH: Analisis Strukturalisme pada Puisi "Salamun Alaikum" karya Anis Susan (Analisis Kritik Sastra) - Yudistira, Wildan; Romadhoni, Moh Syahrul Zaky; Azhari, Faiz (Jazirah: Jurnal Peradaban dan Kebudayaan, 2022)
Semiotics is a branch of linguistics that is important to be studied by students of knowledge in the world. and in one of its theories is structuralism. However, in this study the researcher tried to use the semiotic structuralism theory using a literary criticism approach. the object of research is Arabic literary works, namely poetry by "Anies Syusyan", the purpose of this research to determine of intrinsic elements in the poem "salamun alaikum" by Anies Syusyan, as well as apply literary criticism about the advantages and disadvantages, as well as the quality of the poem "salamun alaikum" by Anies Syusyan. This research is a type of qualitative research, and researcher apply the documentation method in collecting data in this research. Researcher used a descriptive approach and literary criticism to analyze the data in this research. the results of this research are that the intrinsic elements contained in the poem "salamun alaikum" by Anies Syusyan is 6 of the totals. Researcher find the main idea or ideas, feelings or emotions, imagination, style of language, rhyme, and the interrelationships between intrinsic elements. Then, find two strengths and two weaknesses related to intrinsic elements, and determine the reasons to answer the quality of this poem related to intrinsic elements.